Learning Effectiveness Using The Ilearning System (Computer Systems Studies Kampus Merdeka Belajar Kampus Merdeka (MBKM) University of Raharja) - Ageng Setiani Rafika; Ridho Firdaus; Hendra Kusumah; Padeli; Euis Sitinur Aisyah (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2023)
This study aims to make the learning system more modern and can attract students' interest in learning. The learning system that is meant by computer and smartphone-based, students can learn easily and more efficiently. Of course, this research will be useful in the Computer Systems study program at Raharja University. With the iDu 2.0, the learning system in the Computer Systems study program will become even more efficient. Because there will be many more up to date features that will increase student interest in learning. This research model uses a research and development approach. Data collection techniques used are interviews, observation, questionnaires, and skills tests. To analyze the data used technical SWOT analysis. The results of this study explain that a learning system that develops and can increase students' interest in learning, Uses useful technology. Computers are very useful learning media in the present and the future, which of course computers must continue to grow. Keywords: Intelligent Learning (iLearning), Technology , Mobile Learning, Swot